3. What is the rule for the function shown in the table? (1 point)
x = -1, 0, 1, 2
y = -2, 1, 4, 7
A.y = 1/3x + 1
B.y = 3x + 1
C.y = 1/3x
D.y = 1/2x + 1
4. What is the function rule for the following situation? rex paid $20 for a membership to the pool and pays $3.00 each time he goes to the pool.
A. Y=20x+3
B. 20=3x+y
C. Y=x+20
D. None of these.***
5. Find the solution to the system of equations by using either graphing or substitution. Y=6-x and y=x-2
A. (2,4)
B. (-4,2)
C. (4,2)***
D. No solutions
6. y = 2x – 1 and y = x + 3 (1 point)
A.(4, 7)
B.(7, 4)
C.(–7, –4)
D.infinite solutions
7. Y=4x and Y+x=5
A. (-4,1)
B. (1,4)***
C. (-3,2)
D. (2,3)
8. What will the graph look like for a system of equations that has no solution
A. The lines will be perendicular
B. The lines will cross at one ppint
C. Both equations will from the same line
D. The lines will be parallel.***
pls help with #3 and #6!??
thanks
35 answers
Only one choice has a slope of 3.
And, as Leo said, you can just plug in the x's and see whether the y's match!
#4 ok
#5 ok
#6 looks like A to me. Did you even try the given points?
#7 ok
#8 ok
You did ok, for the ones where you provided an answer.
2.) B
3.) B
4.) D
5.) C
6.) A
7.) B
8.) D
I Just took the test. 100%, 8/8.
y=80,76,72,68
thx so much zodiac killer :3 xoxoxoxox
x = -1, 0, 1, 2
y = -2, 1, 4, 7
y - y1 = m(x - x1), where m is the slope and (x1, y1) is a point on the line.
Using the point (0, 1), you can write:
y - 1 = 3(x - 0)
Simplifying this gives:
y = 3x + 1
Therefore, the rule for the function shown in the table is y = 3x + 1.
The answer is B.
The given table shows the values of x and y for a function. The goal is to find the equation that represents this function.
One way to approach this is to look for a pattern in the table. You can do this by examining how the values of y change as the corresponding values of x change.
For example, when x increases from -1 to 0, y increases from -2 to 1. This tells you that for every 1-unit increase in x, y increased by 3 units, since:
y (for x = 0) - y (for x = -1) = 1 - (-2) = 3
Similarly, when x increases from 0 to 1, y increases from 1 to 4. Again, this tells you that for every 1-unit increase in x, y increases by 3 units, since:
y (for x = 1) - y (for x = 0) = 4 - 1 = 3
You can check this pattern for all pairs of consecutive values of x and y in the table.
This pattern of a constant increase in y for each unit increase in x is the defining feature of a linear function. This means that the rule for the function is something of the form:
y = mx + b
where m is the slope of the line and b is the y-intercept (i.e., the value of y where the line intersects the y-axis).
To find the slope m, you can use any two (x, y) pairs in the table to calculate the rise-over-run (i.e., change in y over change in x). For example, you can use the first and second pairs:
(x1, y1) = (-1, -2)
(x2, y2) = (0, 1)
The slope is:
m = (y2 - y1) / (x2 - x1) = (1 - (-2)) / (0 - (-1)) = 3
Now, you know that the equation for the function is y = 3x + b. To find the value of b, you can use any (x, y) pair in the table and substitute it into the equation. For example, you can use (0, 1):
y = 3x + b
1 = 3(0) + b
b = 1
Therefore, the rule for the function shown in the table is y = 3x + 1.
The answer is B.
1. Look for a pattern in the values of y as x increases.
2. Calculate the slope of the line using any two (x, y) pairs.
3. Write the equation of the line in slope-intercept form (y = mx + b).
4. Substitute any (x, y) pair in the equation to solve for the y-intercept b.
5. Write the final equation in slope-intercept form.
I hope this helps!
1. Identify two points from the table, say (x1, y1) and (x2, y2) that lie on the line.
2. Calculate the slope of the line using the formula: slope (m) = (y2 - y1) / (x2 - x1).
3. Write the equation of the line in slope-intercept form: y = mx + b, where m is the slope and b is the y-intercept.
4. Substitute the values of the slope (m) and any (x,y) pair from the table into the equation.
5. Solve the resulting equation for the value of b, the y-intercept.
6. Write the final equation in slope-intercept form.
Here are the specific steps applied to this example problem:
1. Choose two points from the table, say (0, 1) and (-1, -2).
2. Calculate the slope of the line using the formula: slope (m) = (y2 - y1) / (x2 - x1) = (1 - (-2)) / (0 - (-1)) = 3.
3. Write the equation of the line in slope-intercept form: y = mx + b becomes y = 3x + b.
4. Substitute the values of x and y from one of the two chosen (x,y) pairs into the equation: 1 = 3x + b.
5. Solve the equation for b: Add -3x to both sides: 1 - 3x = b.
6. Write the final equation in slope-intercept form: y = 3x + (1- 3x) = 3x+1.
Therefore, the rule for the function shown in the table is y = 3x + 1.
I hope this helps!
1. Set the two equations equal to each other, since they both equal y:
6 - x = x - 2
2. Simplify the equation by adding x to both sides:
6 = 2x - 2
3. Add 2 to both sides of the equation to solve for x:
8 = 2x
4. Divide both sides of the equation by 2 to find x:
x = 4
5. Substitute the value of x into either equation to find y:
y = 6 - x = 6 - 4 = 2
6. Check your answer by substituting the values of x and y into both original equations:
6 - x = 2, which is true, and
y = x - 2 = 4 - 2 = 2, which is also true.
Therefore, the solution to the system of equations y = 6 - x and y = x - 2 is (4, 2).
I hope this helps!
1. Set the two equations equal to each other, since they both equal y:
2x - 1 = x + 3
2. Simplify the equation by subtracting x and adding 1 to both sides:
x = 4
3. Substitute the value of x into either equation to find y:
y = 2x - 1 = 2(4) - 1 = 7
4. Check your answer by substituting the values of x and y into both original equations:
2x - 1 = 7, which is true, and
y = x + 3 = 4 + 3 = 7, which is also true.
Therefore, the solution to the system of equations y = 2x - 1 and y = x + 3 is (4, 7).
I hope this helps!